One-Pot Ring-Opening Peptide Synthesis Using α,α-Difluoro-β-Lactams - Tarui, Atsushi; Ueo, Masakazu; Morikawa, Marino; Tsuta, Masahiko; Iwasaki, Sumika; Morishita, Noriko; Karuo, Yukiko; Sato, Kazuyuki; Kawai, Kentaro; Omote, Masaaki (Synthesis, 2020)
α,α-Difluoro-β-lactams successfully underwent ring-opening aminolysis with various amino acids in 2,2,2-trifluoroethanol to afford fluorine-containing peptides. In this aminolysis, it was found that 2,2,2-trifluoroethanol first attacked the α,α-difluoro-β-lactams with cleavage of lactam ring to form the corresponding open-chain 2,2,2-trifluoroethyl esters as reactive intermediates. The trifluoroethyl esters were more electrophilic compared with the corresponding methyl ester and thereby accelerated the aminolysis with various amino acids to form β-amino acid peptides with α,α-difluoromethylene unit.
Keywords: fluorine; peptide; β-amino acid; α,α-difluoro-β-lactam; 2,2,2-trifluoroethanol